Space optimization of old residential areas based on spatial syntax theory -- Take Changjiang Village, Changchun city as an example - Yan Li; Lin Huiying (E3S Web of Conferences)
Based on the spatial syntactic theory, this paper makes a quantitative analysis of the spatial structure of Changchun Changjiang Village using Depthmap software, discusses the characteristics of the spatial structure, and proposes the corresponding spatial optimization strategies. The research shows that there are some problems in the spatial structure of Changjiang Village, such as poor accessibility and insufficient use of public space. By optimizing the layout of public space, increasing the connectivity of roads and improving the spatial accessibility of roads, the quality of the living environment can be effectively improved to provide a theoretical basis for the reconstruction of the old residential areas.